A new name for Myrmecodesmus potosinus (Shear) 1973, a homonym of Myrmecodesmus potosinus (Chamberlin) 1943 (Diplopoda, Polydesmida, Pyrgodesmidae) - Recuero, Ernesto (Zootaxa, 2014)
The genus Myrmecodesmus was created by Silvestri (1910) to accommodate a small, myrmecophilous polydesmid from central Veracruz. It includes mainly fossorial species and several forms have been collected in caves or associated with ant nests (Silvestri 1911; Shear 1977). Silvestri (1911) described a second species in this genus from the same locality. During subsequent decades several new genera were created as new pyrgodesmid species were described from Mexico, but Myrmecodesmus included only two species until Hoffman (1973) proposed a synonymy with Ilyma Chamberlin, 1941, increasing to seven the number of species referable to Myrmecodesmus. By this time the characters traditionally used to define genera in this family (mostly pore presence and distribution, presence of ozophores, number of segments and ornamentation) started to be questioned (Hoffman 1973; Shear 1973). Finally, a partial taxonomic revision of Pyrgodesmidae from Mexico (Shear 1977) drastically simplified the generic composition of this family and up to 11 genera were introduced into the synonymy of Myrmecodesmus. Including the new combinations, Shear (1977) listed a total of 25 species under this genus, but he missed including a few. This was partly corrected by Hoffman (1999), raising the number to 28 species. However, both authors missed an additional species that implies some nomenclatural issues.